Pengaruh Harga, Citra Merek, dan Kualitas Produk terhadap Loyalitas Pelanggan Gula Pasir Gulaku (Survey Pada Konsumen DM Swalayan Yogyakarta) - Ardhianto Karsa Sunaryono, Ramadhani; Adhi Saputro, Wahyu; Sulistyowati, Ecclisia (Jurnal Bisnis Manajemen dan Akuntansi (BISMAK), 2025)
One of the staples for people's consumption is sugar. Sugar is used as a source of calories and functions as a sweetener. Until now sugar has not been replaced as the main sweetener. The purpose of this study was to determine the effect of price, brand image and product quality on customer loyalty "Gulaku" sugar. This research was conducted with 40 respondents and by accidental sampling method. The questionnaire is used as the main tool for collecting data and using interviews in finding data. This study uses respondents from DM regular customers who buy "Gulaku" sugar products. The analytical method used in this study is multiple linear regression analysis. The analysis shows that price and brand image influence customer loyalty while product quality does not affect customer loyalty.